Homozygous SLC4A11 mutation in a large Irish CHED2 pedigree. (4th March 2017) - Hand, Collette K.; McGuire, Mairide; Parfrey, Nollaig A.; Murphy, Conor C.
ABSTRACT: Background : Congenital hereditary endothelial dystrophy (CHED) is a genetic disorder of corneal endothelial cells resulting in corneal clouding and visual impairment. Autosomal dominant (CHED1) and autosomal recessive (CHED2) forms have been reported and map to distinct loci on chromosome 20. CHED2 is caused by mutations in the SLC4A11 gene which encodes a membrane transporter protein. Materials and methods : Members of a large CHED2 family were recruited for clinical and genetic studies. Genomic DNA was sequenced for the exons and intron-exon boundaries of the SLC4A11 gene. Results : Twelve family members were recruited, of which eight were diagnosed with CHED. A homozygous SLC4A11 mutation (Leu843Pro) was detected in the eight patients; a single copy of the mutation was present in three unaffected carriers. Conclusions : A missense SLC4A11 mutation (Leu843Pro) is responsible for CHED2 in this family; this is the first report of this mutation in a homozygous state.